PADDY-POTATO-WHEAT: A PROMISING CROPPING SEQUENCE FOR KYMORE PLATEAU OF MADHYA PRADESH - Kushwah, S. S.; Dwivedi, Y. C.; Jain, P. K. (Potato Journal, 2013)
An investigation on cropping sequence consisting of six combinations of paddy, wheat, radish, methi and cauliflower crops and two crop durations of potato (65 and 75 days) was conducted at farmers’ field of Katni and Jabalpur districts during 2000-01, 2001-02 and 2002-03. Among the six cropping sequences, paddy-potato (75 days)-wheat sequence maximized PYE (426.17 q/ha) with a 249.32% increase over paddy-wheat sequence with maximum net return of Rs. 68,400 /ha.